Case Report: Multiple Vertebral Compression Fractures in 14-Year-Old Children With Multiple Myeloma - Wang, Xia; He, He; Zhang, Mei; Li, Chuan; Jia, Chengyao (Frontiers in Oncology, 2021)
Multiple myeloma (MM) is a neoplastic disorder characterized by clonal proliferation of malignant plasma cells derived from B cells in bone marrow. Pediatric MM is rare with only approximately 0.3% of cases diagnosed before the age of 30. In this report, we present a 14 years old boy diagnosed as MM with multiple pathologic vertebral fractures. To our knowledge, our patient is the youngest Chinese case in the literature to present with MM. He was treated with bortezomib, dexamethasone, and cyclophosphamide followed by autologous hematopoietic stem cell transplantation with good clinical response. We hope to aid in the understanding of the pathophysiology and management of this condition.